1996
DOI: 10.1108/02683949610150042
|View full text |Cite
|
Sign up to set email alerts
|

Job applicant past performance, interpersonal attraction and evaluator attributions in the selection decision process

Abstract: Examines the interactive effects of applicant past performance, evaluator attributions and interpersonal attraction on selection decisions. A total of 172 male and female students evaluated an application for an on‐campus position and were asked to make selection decisions. Results indicated that internal attributions for good past performance were associated with more favourable selection decisions while internal attributions for poor past performance were associated with less favourable selection decisions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
(27 reference statements)
0
8
0
1
Order By: Relevance
“…Another key similarity element refers to the perceived similarity in attitudes, values, perspectives and work habits between raters and ratees. Research examining this factor generally supports Byrne's (1971) view of the relationship between interpersonal attraction or liking and attitudinal similarity (Phillips and Phillips, 1996). That is, attitudinal similarity implies a level of interpersonal attraction or general agreement in views that people find rewarding.…”
Section: Interpersonal Liking and Ratingsmentioning
confidence: 57%
“…Another key similarity element refers to the perceived similarity in attitudes, values, perspectives and work habits between raters and ratees. Research examining this factor generally supports Byrne's (1971) view of the relationship between interpersonal attraction or liking and attitudinal similarity (Phillips and Phillips, 1996). That is, attitudinal similarity implies a level of interpersonal attraction or general agreement in views that people find rewarding.…”
Section: Interpersonal Liking and Ratingsmentioning
confidence: 57%
“…Additionally, the similarity hypothesis has been tested beyond laboratory settings where the controlled conditions and the use of bogus strangers limited the generalizability of initial findings. These investigations indicate that similarity accounts for decisions in such organizational settings as performance evaluations (Strauss, Barrick, & Connerley, 2001;Zalesny & Kirsch, 1989), selections (Phillips & Phillips, 1996), negotiations (Graham, Kim, Lin, & Robinson, 1988), and leader-follower relationships (Ashkanasy & O'Connor, 1997). Together, these investigations provide support for the pervasive effect of similarity attraction.…”
Section: Figure 1 Results For Tests Of the Process Modelmentioning
confidence: 82%
“…Partners use only a small portion of their allocated time for decision making, and sometimes may be subject to bias (Arvey and Campion, 1982; James and Otsuka, 2009). Past research in psychology has demonstrated that interviewers are influenced by variables including first impressions (dress effect), physical attractiveness, interpersonal attraction, perceived similarity, subjective qualifications, objective qualifications, gender, and attitudes (Byrne, 1971; Keenan, 1977; Gilmore et al , 1986; Raza and Carpenter, 1987; Graves and Powell, 1988; Morrow, 1990; Sharp and Post, 1980; Phillips and Phillips, 1996; Anderson‐Gough et al , 2005; Jawahar and Mattsson, 2005; Hanson and Giannantonio, 2006; Kimmell et al , 2008; Rudolph et al , 2009). However, prior studies have conducted interviewing research based mainly on artificial experimental conditions rather than using actual employment interviews (Cann et al , 1981; Gilmore et al , 1986; Sharp and Post, 1980; Phillips and Phillips, 1996; Jawahar and Mattsson, 2005; Rudolph et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Through a review of the literature (Byrne, 1971; Cohen and Bunker, 1975; Dipboye et al , 1977; Pulakos and Wexley, 1983; Raza and Carpenter, 1987; Graves and Powell, 1988; Morrow, 1990; Sharp and Post, 1980; Phillips and Phillips, 1996; Anderson‐Gough et al , 2005; Jawahar and Mattsson, 2005), seven main independent variables are identified: namely:subjective qualifications;objective qualifications;interpersonal attraction;physical attractiveness;perceived similarity;dress effect; andgender.The dependent variables in this study included:offer subject to further interview group;offer group; andreject group.This study is also the first to use a sophisticated statistical analysis method, multinomial logistic regression, to analyze the new research design. Given the theoretical underpinnings of the present study and the lack of prior studies, it is believed that the results of this study will make a contribution to an understanding of the hiring decisions of experienced auditors in public accounting practices.…”
Section: Introductionmentioning
confidence: 99%